Sosialisasi Perlindungan Hak Anak dalam Perceraian Menurut Hukum Perdata di Kampung Tinggar Jalan, RT 03 RW 02, Kelurahan Sukalaksana, Kecamatan Curug, Kota Serang, Provinsi Banten - Medina, Farah; Ayu Pramisti, Dinda; Nisa Nur Sabila, Uhtia; Alam Muluk, A.M. Alam Bagus; Fartini, Ade (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
This community service activity aims to enhance public understanding of children’s rights in divorce cases under civil law. The implementation method used was an interactive lecture delivered directly to the residents of Kampung Tinggar Jalan, RT 03 RW 02, Sukalaksana Village, Curug District, Serang City, Banten Province. Through this activity, participants gained knowledge about the position and protection of children’s rights, which are often neglected during divorce processes, including rights to custody, education, and welfare. The results indicated that residents were able to identify and comprehend children’s rights according to Indonesian civil law. This activity contributes to raising public legal awareness and encouraging active participation in protecting children’s rights after divorce.